2017
DOI: 10.1016/j.ebiom.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Tenomodulin is Required for Tendon Endurance Running and Collagen I Fibril Adaptation to Mechanical Load

Abstract: Tendons are dense connective tissues that attach muscles to bone with an indispensable role in locomotion because of their intrinsic properties of storing and releasing muscle- generated elastic energy. Tenomodulin (Tnmd) is a well-accepted gene marker for the mature tendon/ligament lineage and its loss-of -function in mice leads to a phenotype with distinct signs of premature aging on tissue and stem/progenitor cell levels. Based on these findings, we hypothesized that Tnmd might be an important factor in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
69
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 68 publications
8
69
0
1
Order By: Relevance
“…In contrast to our previous results, we found out that Tnmd −/− OAF contain collagen fibrils with smaller calibers and lower compressive stiffness, which cannot provide enough strength and proper load distribution over large parts of the OAF. According to these results and our previous finding that Tnmd is a mechanosensitive and mechanoregulated gene (Dex et al, ), we propose that the above‐described phenotypic differences between tendon and IVD tissues are the consequence of the different biomechanical environments, namely IVDs are subjected mainly to compressive stress while tendons to tensile forces.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In contrast to our previous results, we found out that Tnmd −/− OAF contain collagen fibrils with smaller calibers and lower compressive stiffness, which cannot provide enough strength and proper load distribution over large parts of the OAF. According to these results and our previous finding that Tnmd is a mechanosensitive and mechanoregulated gene (Dex et al, ), we propose that the above‐described phenotypic differences between tendon and IVD tissues are the consequence of the different biomechanical environments, namely IVDs are subjected mainly to compressive stress while tendons to tensile forces.…”
Section: Discussionsupporting
confidence: 74%
“…In our previous studies, we compared Tnmd knockout ( Tnmd − / − ) mice with their wild‐type (WT) littermates and showed that the absence of Tnmd causes reduced tendon cell proliferation and density in vivo (Docheva et al, ), coupled with significantly lower self‐renewal and augmented senescence of tendon‐derived stem/progenitor cells (TSPCs) in vitro (Alberton et al, ). Furthermore, we observed the pathological thickening and stiffening of collagen I (Col I) fibers in Tnmd − / − Achilles tendons resulting in running distance and time failure in Tnmd − / − mice challenged by running tests (Dex et al, ). Interestingly, the local absence of Tnmd in the cardiac chordae tendineae cordis (CTC) promoted angiogenesis and matrix metalloproteinases (MMPs) activation (Kimura et al, ), a phenomenon also observed when Tnmd − / − mice were subjected to surgically induced Achilles tendon rupture.…”
Section: Introductionmentioning
confidence: 99%
“…The role of integrin-linked kinase (ILK) in skeletal muscles and tenomodulin (TNMD/Tnmd) in tendons was assessed using a conditional KO model 3 and a constitutive KO mouse model, respectively. 4 Integrin-linked kinase is a protein highly expressed in skeletal muscle, more precisely at myotendinous junctions (MTJs). The principal function of MTJs is to bind myofibers to tendons and therefore it is relevant for proper force transmission.…”
mentioning
confidence: 99%
“…It has been recently reported that Tnmd is needed for optimal running performance. 4 Mice lacking Tnmd failed in forced endurance running tests (daily treadmill exercise for 60min. at 10m/min with a declination of 10°).…”
mentioning
confidence: 99%
See 1 more Smart Citation